Acute Myocardial Infarction in a Young Lady due to Vitamin B12 Deficiency Induced Hyperhomocysteinemia - Shamkani, Warkaa Al (Heart Views, 2015)
Hyper-homocysteinemia is a risk factor for coronary artery disease in young patients. A 32 years old female without any conventional risk factors except obesity presented with acute anterior wall myocardial infarction (MI). Her echocardiography showed anterior wall hypokinesia with moderate left ventricular dysfunction. Angiography showed tight stenosis of the proximal left anterior descending (LAD) and borderline lesion in left circumflex coronary artery (LCX). She underwent percutaneous coronary intervention (PCI) to LAD with good result. Her blood tests showed low vitamin B12, folate and serum iron levels and elevated serum homocysteine level. She was given folic acid and vitamin B12 and her homocysteine levels normalized. This case demonstrates that hyperhomocysteinemia caused by nutritional deficiency of vitamin co factors may lead to MI. Hyperhomocysteinemia should be considered in the evalauation of young people with MI, especially those without conventional risk factors.